Internalizing the social costs of smoke emissions into strategic fuels planning models - Rossi, David J., author; Rideout, Douglas, advisor; Wei, Yu, committee member; Kling, Robert, committee member; Kirsch, Andy, committee member (Colorado State University. Libraries, 2016)
Emissions of fine particulate matter from prescribed burns are a growing concern for wildland fire managers. Stringent air quality regulations and community discern over the emissions from prescribed fire smoke often severely restrict the ability to implement restorative and precautionary fuels treatments. While some extent of emissions are unavoidable, strategic planning can help reduce their impacts. Estimating the cost of smoke and incorporating it into landscape level fire planning may reduce the burden on wildland fire officials confronted with a complex set of choices and constraints. Currently, no decision-support systems are available for strategically incorporating the cost of smoke in fire planning at the landscape level. A decision model is developed to address this void by estimating the value of fire and fuels management at the landscape level by including the cost of smoke in cellular level estimates social returns. By working with locally defined emission standards and translating them into a cost per unit of smoke impact, I was able to internalize the external impact of smoke emissions into a strategic fuels planning model by reprioritizing the optimal selection of landscape grid cells to target for prescribed fire investments. This has the potential to aid the fire planner in analyzing trade-offs for prescribed fire management. In a case study at King's Canyon National Park, emissions standards are used to estimate a relative unit cost of impact (per unit of emissions). The unit cost is subtracted from cellular estimates of marginal social returns to re-prioritize the spatial design of landscape scale fuel treatments.